Preparation method of magnesium-based graphene absorbable stent composite material

Through the preparation method of magnesium-based graphene composite materials, the problem of insufficient mechanical properties and corrosion resistance of magnesium-based materials is solved, and the preparation of composite materials with high efficiency, low cost and stable performance is achieved, which is suitable for multiple technical fields.

CN119392030APending Publication Date: 2025-02-07SU ZHOU XIANG QIN YI LIAO KE JI YOU XIAN GONG SI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410156908.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-02-04
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing magnesium-based materials have problems with insufficient mechanical properties and corrosion resistance as intravascular absorbable stents, and the existing preparation technology is costly, low efficiency and unstable in performance.

Method used

A method of preparing a magnesium-based graphene absorbable scaffold composite material, including graphene ultrasonic treatment, magnesium-based material preparation, ball milling processing, vacuum drying, composite pressing die, microwave sintering, high-pressure synthesis and solid-temperature extrusion, etc. .

Benefits of technology

Through this preparation method, the obtained magnesium-based graphene composite material has excellent mechanical properties, thermal conductivity and electrical conductivity, low cost, high efficiency and stable performance, and is suitable for medicine, aerospace, automobiles and electronic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392030A_ABST
    Figure CN119392030A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a magnesium-based graphene absorbable stent composite material. The preparation method comprises the following steps: step 1, ultrasonic treatment of graphene; 2, preparing raw materials of the magnesium-based material; step 3, ball milling processing; step 4, vacuum drying; 5, composite die pressing is carried out; step 6, microwave sintering; step 7, performing high-pressure synthesis; and 8, carrying out solid temperature extrusion. According to the preparation technology of the magnesium-based graphene composite material, the performance of the composite material can be adjusted by controlling the addition amount of the graphene, the temperature and time of the heating reaction, the conditions of high-pressure deposition and the like, the dispersity and compatibility of the graphene with magnesium powder, zinc powder and calcium powder can be improved by adopting the organic solvent and the coupling agent, and the magnesium-based graphene composite material is prepared. The preparation technology is simple in process, low in cost and high in efficiency, and the prepared magnesium-based graphene composite material has excellent mechanical properties, heat conductivity and electric conductivity and can be widely applied to the technical fields of medicine, aerospace, automobiles and electronic products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite material preparation, in particular to a method for preparing a magnesium-based graphene absorbable stent composite material. Background Art

[0002] Graphene, a two-dimensional material formed by a single layer of carbon atoms arranged in a honeycomb structure, has attracted widespread attention due to its excellent mechanical, electrical and thermal properties. As a potential reinforcement material, graphene has excellent mechanical and physical properties, an average thickness of 5-10μm, and a specific surface area of ​​1200 to 1450m2 / g. Based on the excellent physical and chemical properties of graphene, people hope to use one or some of its characteristics to enhance the performance of the metal matrix.

[0003] Magnesium is silvery white, soft and light, with a melting point of 649°C and a density of 1.74g / cm3. It has strong chemical activity, a strong affinity with oxygen, and is easily soluble in organic and inorganic acids. Magnesium can directly combine with nitrogen, sulfur, and halogens. Metallic magnesium is non-magnetic and has good heat dissipation. Adding graphene to the magnesium matrix can effectively improve the linear expansion and thermal stability of magnesium alloys, and improve the mechanical properties of the alloy such as tensile strength. At present, the preparation process of magnesium-based composite materials needs to be improved and perfected, and constructive research on its accurate composite mechanism and strengthening mechanism at the interface needs to be deepened.

[0004] Graphene is a two-dimensional material with special structure and properties. It has good biocompatibility. Studies have shown that it does not cause obvious toxicity or immune response in the body. Graphene has anticoagulant and antiplatelet aggregation effects. This may be due to the special structure and chemical properties of the graphene surface, which can interact with coagulation factors and platelets in the blood, thereby reducing the risk of thrombosis. In addition, graphene can inhibit the proliferation and migration of smooth muscle cells, which is of great significance for preventing restenosis of blood vessels after stent surgery. Graphene may play this role by regulating cell signaling pathways and inhibiting the expression of cell proliferation-related genes. As a material for intravascular absorbable stents, graphene's role in inhibiting smooth muscle cell proliferation and migration can help reduce the risk of restenosis. In addition, the high strength and flexibility of graphene also contribute to the plasticity of stent processing and the stability and durability after implantation.

[0005] It should be pointed out that as a new material, the research on graphene in the field of intravascular absorbable stents is still in its early stages. Further and larger-scale clinical research and verification are needed for the anticoagulant, antiplatelet, smooth muscle cell proliferation inhibition and restenosis prevention effects of graphene stents.

[0006] In order to overcome the shortcomings of magnesium-based materials such as mechanical properties and corrosion resistance as intravascular absorbable stents, researchers are committed to developing graphene-reinforced magnesium-based composites. However, the existing preparation technology has problems such as high cost, low efficiency, and unstable performance. Therefore, it is of great significance to develop an efficient, low-cost, and stable performance magnesium-based graphene composite preparation technology. Summary of the invention

[0007] The purpose of the present invention is to solve the above problems and to design a method for preparing a magnesium-based graphene absorbable stent composite material.

[0008] To achieve the above object, the technical solution of the present invention is a method for preparing a magnesium-based graphene absorbable stent composite material, comprising the following steps:

[0009] Step 1: ultrasonic treatment of graphene;

[0010] Step 2: Preparation of raw materials of magnesium-based materials;

[0011] Step 3: ball milling;

[0012] Step 4: vacuum drying;

[0013] Step 5: Composite die pressing;

[0014] Step 6: microwave sintering;

[0015] Step 7: high pressure synthesis;

[0016] Step 8: Solid temperature extrusion.

[0017] As a further description of the technical solution, in the step 1, the graphene includes graphene materials of different properties such as multilayer graphene oxide (MGO), multilayer graphene nanosheets (GNS), and carbon nanotubes (CNT), and the fine-layer graphene is ultrasonically treated and extracted, and the graphene is dissolved in ethanol (100-200 mg / ml) and ultrasonically dispersed for 1 hour.

[0018] As a further description of the technical solution, in the step 2, the magnesium-based material pure magnesium and magnesium alloys of various components, the ultrasonically treated graphene are mixed with a certain proportion of pure magnesium or magnesium alloy powder to obtain a magnesium-based graphene mixture, the graphene content is usually 0.1-3wt%, and an appropriate amount of water and ethanol are added as a medium (the ratio of ethanol to magnesium alloy is 1-2g / ml), and stirred for 60-120 minutes to obtain a uniform slurry.

[0019] As a further description of the present technical solution, in the step three, the magnesium-based graphene mixture is placed in a ball mill, and appropriate amounts of water and ethanol are added as media, the ball-to-material ratio is 10:1, the ball mill speed is 300 rpm, and the ball milling time is 1-3 hours; a 10 mm tungsten carbide ball is used.

[0020] As a further description of the technical solution, in step 4, vacuum drying is performed at 80° C. for 2 hours.

[0021] As a further description of the technical solution, in step 5, a homogeneous composite mixture with different graphene percentages (such as 1wt%, 2wt%, 3wt%) is mixed with a zinc stearate binder and polyvinyl alcohol (PVA) as a functional agent, and compacted with a steel mold at a pressure of 500MPa for 3-5min to obtain a certain size such as of the green body.

[0022] As a further description of the technical solution, in step six, the green body is sintered in a microwave oven for 15-30 minutes in an environment where argon inert gas continuously exists.

[0023] As a further description of the technical solution, in step seven, combined with high-pressure synthesis technology, in a high-pressure reactor, the temperature is 300-500°C, the pressure is 1000-5000psi, and the synthesis time is 2-12 hours.

[0024] As a further description of the technical solution, in step eight, hot extrusion is performed at 300-400°C, the extrusion speed is 1-2mm / Sec, and the extrusion ratio is 11:1 to eliminate porosity and increase the density of the composite material, and finally obtain the required wire.

[0025] As a further description of the technical solution, the prepared magnesium-based graphene composite material is applied to related technical fields such as medical, aerospace, automobile and electronic products.

[0026] The beneficial effect lies in that the preparation technology of the magnesium-based graphene composite material provided by the present invention can adjust the performance of the composite material by controlling the addition amount of graphene, the temperature and time of the heating reaction, and the conditions of high-pressure deposition, etc. At the same time, the use of organic solvents and coupling agents can improve the dispersibility and compatibility of graphene with magnesium powder, zinc powder and calcium powder, and improve the performance of the composite material. The preparation technology has the advantages of simple process, low cost, high efficiency, etc. The prepared magnesium-based graphene composite material has excellent mechanical properties, thermal conductivity and electrical conductivity, and can be widely used in the fields of medicine, aerospace, automobiles, electronic products, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the morphology of graphene received before the experiment. Figure 1 A. FE-SEM image of graphene nanosheets at 18kx, Figure 1 B HR-TEM observation of graphene at 2500×, Figure 1 C. Graphene observed by HR-TEM at 14,500×;

[0028] Figure 2 is the electron diffraction pattern of graphene obtained from HR-TEM;

[0029] Figure 3 These are the FESEM images of P-Mg, AZ31 and Mg-Zn-Ca (ZX20) powders as received before treatment; A: P-Mg, B: AZ31 and C: Mg-Zn-Ca (ZX20);

[0030] Figure 4 It is the Fourier transform infrared (FTIR) peak of microwave processed and hot extruded composite materials. A: P-Mg, B: AZ31 and C: Mg-Zn-Ca (ZX20);

[0031] Figure 5 EBSD images of 2wt% Gr composites under microwave sintering conditions; A: P-Mg, B: AZ31 and C: Mg-Zn-Ca (ZX20);

[0032] Figure 6 are the EBSD images of 2wt% Gr composites after hot extrusion; A: P-Mg, B: AZ31 and C: Mg-Zn-Ca (ZX20);

[0033] Figure 7 HR-TEM analysis of graphene embedded in composite matrix; A: P-Mg, B: AZ31 and C: Mg-Zn-Ca (ZX20);

[0034] Figure 8 It is the yield strength data graph of microwave processed hot extruded graphene nanocomposites;

[0035] Fig. 9 is the stress-strain curve of ZX20+wt%of Graphene;

[0036] Fig.10 These are SEM images showing concave rupture on the tensile fracture surface; A: P-Mg, B: AZ31, and C: Mg-Zn-Ca (ZX20).

[0037] Fig.11 It is a comprehensive hardness diagram of different grades of graphene-reinforced magnesium alloy composites. DETAILED DESCRIPTION

[0038] First of all, the original intention of the design of the present invention is explained. In order to overcome the shortcomings of magnesium-based materials as intravascular absorbable stents in terms of mechanical properties and corrosion resistance, researchers are committed to developing graphene-reinforced magnesium-based composite materials. However, the existing preparation technology has problems such as high cost, low efficiency, and unstable performance. Therefore, the present invention designs a method for preparing a magnesium-based graphene absorbable stent composite material.

[0039] The present invention will be described in detail below in conjunction with the accompanying drawings. Figure 1 As shown, a method for preparing a magnesium-based graphene absorbable stent composite material comprises the following steps:

[0040] Step 1: ultrasonic treatment of graphene; in the step 1, graphene includes graphene materials of different properties such as multilayer graphene oxide (MGO), multilayer graphene nanosheets (GNS), and carbon nanotubes (CNT), and fine-layer graphene is ultrasonically treated and extracted, and the graphene is dissolved in ethanol (100-200 mg / ml) and ultrasonically dispersed for 1 hour.

[0041] Step 2: Preparation of magnesium-based material raw materials; in the step 2, the magnesium-based material pure magnesium and magnesium alloys of various components, ultrasonically treated graphene and a certain proportion of pure magnesium or magnesium alloy powder are mixed to obtain a magnesium-based graphene mixture, the content of graphene is usually 0.1-3wt%, and appropriate amounts of water and ethanol are added as media (the ratio of ethanol to magnesium alloy is 1-2g / ml), and stirred for 60-120 minutes to obtain a uniform slurry.

[0042] Step three: ball milling; in the step three, the magnesium-based graphene mixture is placed in a ball mill, and appropriate amounts of water and ethanol are added as media, the ball-to-material ratio is 10:1, the ball milling speed is 300 rpm, and the ball milling time is 1-3 hours; a 10 mm tungsten carbide ball is used.

[0043] Step 4: vacuum drying; in the step 4, vacuum drying is performed at 80° C. for 2 hours.

[0044] Step 5: Composite compression molding; In step 5, a homogeneous composite mixture with different graphene percentages (1wt%, 2wt%, 3wt%) is mixed with a zinc stearate binder and polyvinyl alcohol (PVA) as a functional agent, and compacted with a steel mold at a pressure of 500MPa for 3-5min to obtain a certain size such as of the green body.

[0045] Step six: microwave sintering; in step six, the green body is sintered in a microwave oven for 15-30 minutes in an environment where argon inert gas continuously exists.

[0046] Step seven: high pressure synthesis; in step seven, combined with high pressure synthesis technology, in a high pressure reactor, the temperature is 300-500°C, the pressure is 1000-5000psi, and the synthesis time is 2-12 hours.

[0047] Step eight: hot extrusion; in step eight, hot extrusion is performed at 300-400°C, the extrusion speed is 1-2 mm / Sec, and the extrusion ratio is 11:1 to eliminate porosity and increase the density of the composite material, and finally obtain the required wire.

[0048] The prepared magnesium-based graphene composite materials are used in related technical fields such as medical, aerospace, automobiles and electronic products.

[0049] Dispersion of graphene in magnesium alloy matrix: Graphene has excellent mechanical and electrical properties, but its dispersion in magnesium alloy matrix is ​​the key issue in the preparation of graphene-reinforced magnesium alloy-based composites by powder metallurgy. In order to achieve uniform dispersion of graphene in magnesium alloy matrix, ball milling, ultrasonic dispersion and other methods are used to pretreat graphene to improve its dispersibility in magnesium alloy matrix.

[0050] In the metallurgical process, zinc stearate binder and polyvinyl alcohol can be mixed and used as functional agents. The amount can be calculated based on specific application requirements and test results. The following is some basic information and usage of zinc stearate binder and polyvinyl alcohol:

[0051] 1. Zinc stearate binder: Zinc stearate is an organic acid salt, commonly used as a binder and lubricant. It can increase the bonding force and lubrication between material particles in the metallurgical process, and help form bulk materials. The amount of zinc stearate can be adjusted according to factors such as material characteristics, particle size distribution, humidity, etc., and is generally determined through experiments and actual production experience.

[0052] 2. Polyvinyl alcohol: Polyvinyl alcohol is a water-soluble polymer compound with good adhesion and solubility. In the metallurgical process, polyvinyl alcohol can be used as a binder to help increase the adhesion and strength of the material. The amount of polyvinyl alcohol can also be determined based on the characteristics of the material and test results.

[0053] Zinc stearate binder and polyvinyl alcohol can be used alone or in combination in the metallurgical process, depending on the desired effect and process requirements; when used in combination, the ratio and amount of the two can be determined based on tests and actual conditions to achieve the best bonding effect and process requirements.

[0054] Figure 1 is the graphene morphology as received before treatment (finite element scanning electron microscope FE-SEM);

[0055] FE-SEM image of graphene nanosheets obtained before treatment at 18kx magnification ( Figure 1 In Figure A), it can be observed that graphene has a quasi-two-dimensional sheet structure; graphene has a huge surface area with a specific surface area (SSA) of 1200 to 1450 m2 / g; the large surface area of ​​graphene provides high wettability and contact area; this plays a key role in the wettability of graphene nanosheets as a reinforcer for the matrix material; the graphene layers are stacked one by one into agglomerates; however, in order to prevent the agglomeration of graphene sheets, it is necessary to ultrasonically treat the graphene during the manufacturing process.

[0056] Graphene morphology before and after exfoliation (High-resolution transmission electron microscopy HR-TEM) HR-TEM is a powerful tool for analyzing the morphology and structural characteristics of graphene from micrometer to nanometer scales; images at 2500× resolution show, e.g. Figure 1 In middle B, a single layer of graphene sheets has wrinkles and folds, also visible at a higher magnification of 14,500×; in Figure 1 C, Imaging conditions were set to expose single-layer carbon atoms in white and stacked monolayer (bilayer) atomic contrast in black. The wrinkles observed in the graphene sheets will have an adverse effect on the strength and stiffness properties of the composites. These wrinkles may be the result of out-of-plane bending phonons or static wrinkling phenomena, which may be caused by the inhomogeneous stress concentration experienced during the graphene production process and will lead to degradation of mechanical properties when reinforced into the fabricated composites in their current form.

[0057] Figure 2 The ED mode pattern obtained by observing the graphene flakes is shown, and more intense spots are recorded in the inner ring than in the outer ring, confirming the presence of single-layer graphene flakes. In the presence of double-layer graphene flakes, the outer ring is observed to be more intense, which also correlates well with the SAED pattern.

[0058] Magnesium alloy powder morphology

[0059] The morphological characteristics of the magnesium alloy powder, such as particle shape, size, texture and surface area, were analyzed using FESEM; the magnesium powder was spherical; spherical and round particles had good apparent density and flow rate, and had a small angle of repose, thereby achieving good flow rate and bonding and friction between particles; in the present invention, the average particle size of the ultrafine magnesium powder was in the range of 10-25 μm; for spherical powders, the particle size was characterized according to its diameter.

[0060] Particle shape and size play an important role in the final properties of the material; the resulting grain size analysis is a fundamental characteristic of the powder particles, which affects other parameters such as material flow rate, apparent density, machinability, compressibility and formability; obtaining an ultrafine grain microstructure can improve mechanical properties such as ultimate tensile strength, compression and fracture strength, elongation at failure, tensile and compression Young's modulus, shear modulus, density, and ultimately improve thermal properties such as thermal conductivity, specific heat capacity and thermal expansion coefficient; the Hall-Page equation emphasizes the same relationship between the final grain size and the recorded yield stress expressed in equation (1), where a decrease in grain size will increase the strength of the material. Fine metal powders have poor apparent density, low flow rate and high sinterability, while coarse powders have high apparent density and flow rate, but reduced sinterability.

[0061] σy = σ0 +ky / √d (1)

[0062] FE-SEM / EDS Analysis of Microwave Processed and Hot Extruded Nanocomposites

[0063] In selected areas, EDS analysis of the composites under FE-SEM revealed that the alloying elements formed stable intermetallic precipitates and dendrites. Graphene was clearly present in the matrix analyzed by EDS. FE-SEM also revealed that graphene agglomerates at >2% weight ratio, and reinforcements agglomerate less in wt1% Gr. The agglomeration of graphene can have an adverse effect on mechanical and other properties, but we found that the introduced graphene reinforcements are uniformly mixed and dispersed in the matrix of microwave processed and hot extruded composites.

[0064] X-ray Diffraction (XRD) Analysis of Composite Materials

[0065] Using X-ray diffraction (XRD), the compounds formed during and after the manufacturing process were analyzed to identify the elements and potential crystal structures formed by alloying elements and reinforcement materials in the magnesium alloy graphene composite material; the XRD spectrum reads the crystal structure of the material based on the lattice parameters of the material, and the XRD results obtained directly from the device can read the peaks of the corresponding elements; it is worth noting that carbon has a hexagonal crystal structure and the graphene of the composite material has been recorded as a rhombohedral crystal structure; this may be due to the stacking of single layers of graphene; regardless of the alloy matrix used, after the hot extrusion process, after the microwave processing technology, it was observed that the properties of graphene were retained, forming natural flakes with high activation energy at the crystal interface and precipitation interface, showing low-strength formed carbon compounds, which is very beneficial for applications in the biomedical field that require good mechanical properties.

[0066] Fourier transform infrared (FTIR) peaks of microwave processing and hot extrusion

[0067] Fourier transform infrared (FTIR) spectroscopy is widely used for elemental analysis of various inorganic materials, organic matter, polymers and two or more compounds; FTIR peaks of microwave processing and hot extrusion such as A: P-Mg+Gr, B: AZ31+Gr and C: Mg-Zn-Ca(ZX20)+Gr Figure 4 As shown, the sp stretching vibration 2C=C-specific bond peak appears at 1680cm in AZ31+2wt%Gr and P-Mg+2wt%Gr materials, which is the asymmetric sheet carbon-1 formed by graphene nanoparticles (GNPs); however, in the spectrum recorded for Mg-Zn-Ca(ZX20)+2wt%Gr composite material (β), a similar peak carbon-1 appears at 1650cm, indicating that the material has a stronger intensity and shows the form of exfoliated GNPs; this characteristic phenomenon may be related to the interaction between the sheet graphene carbon atoms and the incident light, and the more extensive and potential reason is due to the exfoliation process caused by the hot extrusion of the composite material after ultrasonic and microwave treatment. The enhanced nano-GNPs do not show any reaction and transformation of the intermetallic compound group, and the absorption band therein may be due to the edge of the solid sample during the FTIR detection process.

[0068] Electron Backscatter Diffraction (EBSD) Analysis of Composite Materials

[0069] EBSD data show important information of composite materials, such as average grain diameter, grain elongation and orientation angle, as well as pole figures, grain boundaries and crystal structure orientation; Figure 5 Figures AC show the EBSD images of 2wt% Gr composites under microwave sintering conditions, confirming the ultrafine grain structure and finding higher grain orientation along the hybrid (101), (111) and (001) composite microstructures, as most of the prepared composites have an average grain size of 10–25μm. This confirms that excellent interfacial bonding between magnesium and nanographene is achieved through microwave processing and hot extrusion processes, which is again clearly confirmed from HR-TEM analysis.

[0070] Figure 6 It is shown in Figure 2 that the hot extrusion process induces a slight elongation of the grain boundaries, resulting in surface defects such as closure of micropores after the microwave sintering process; however, the presence of graphene clearly gives the microstructure of the composite a fine grain structure; this can be attributed to the fact that the added reinforcement acts as an inhibitor of g-rain growth (pinning effect); the high specific surface area (SSA) of graphene leads to the formation of finer grains, and the volume of the number of atoms in contact with the nucleating agent increases with graphene, which can be given by equation (2).

[0071]

[0072] Where r is the radius of the particle and f is the volume fraction (dispersed phase).

[0073] However, the refined grains are dependent on time distribution and temperature, and depend on the critical size of the particles; these extruded samples produce elongated particles together with graphene during extrusion along the metal flow direction, but when the weight ratio of graphene is greater than 2wt%, the agglomeration of particles is shown in the EBSD map; these agglomerations weaken the grain boundaries. The dispersed graphene particles are more clearly visible at higher magnifications, and graphene does not react with the phases and alloying elements present in the microstructure and remains as heterogeneous particles.

[0074] HR-TEM analysis of composite materials

[0075] Figure 7 A-C show graphene embedded in a composite matrix, respectively; the composite is integrated with nanolayered graphene (single-atom thickness), which reduces the spacing between the metal layers and helps improve strength.

[0076] In graphene-reinforced materials, grain growth is interrupted mainly due to the re-nucleation of graphene, resulting in a finer grain structure; the pinning effect of added graphene prevents the growth of the composite material, and graphene acts as a nanoscale filler, thereby minimizing defects in the matrix material, such as point defects, line dislocations and surface defects; the interface between the matrix and graphene is actually interlocked.

[0077] Figure 7 Also shown are the precipitates found in the alloy matrix, which are responsible for increasing the material's strength. These precipitates resist the movement and rearrangement of dislocations through pinning forces. The best dislocation pinning forces were achieved compared to graphene, which stabilizes the microstructure by trapping mobile dislocations. The two main challenges in fabricating Mg-Gr composites are the formation of magnesium carbide with graphene, and surface contamination of magnesium oxide powder.

[0078] Our study also confirmed that there was no carbide formation in the composite matrix. The possibility of carbide formation may be due to several factors, including (i) the maximum solubility of carbon in magnesium, (ii) the sensitivity of alloying elements in the matrix material and (iii) the reaction kinetics of magnesium and carbon at high temperatures. It is reported that the maximum solubility of carbon in magnesium is 0.02-0.03wt%. In addition, the sintering temperature during the manufacturing process was maintained at 450℃, which may be the possible reason for obtaining carbide-free composites.

[0079] Reducing oxide formation is another challenging task that can be addressed by making the composite mixture in a vacuum / inert atmosphere glove box and preheating the powder to remove any organic and hydrogen contaminants. Ball milling also destroys this oxide film. However, considering all these precautions, the formation of oxides and carbides is negligible.

[0080] Tensile study analysis

[0081] like Figure 8 The results of the tensile test show that the magnesium alloy reinforced by 2wt% graphene shows the greatest strength; the maximum tensile strengths of magnesium alloy + 2wt% Gr are P-Mg 243.76MPa (mother alloy YS187MPa), AZ31 268.31MPa (mother alloy YS183MPa) and ZX20 321.17MPa (mother alloy YS223MPa). Fig. 9 The alloy showed a high degree of conductivity, about 20.83%. Tensile analysis clearly showed that the tensile strength of magnesium alloys can be increased by 25-30% when properly reinforced with graphene nanosheets.

[0082] The increase in tensile strength demonstrates the effect of adding graphene as a suitable and promising reinforcement material in the original alloy. At the same time, the improvement in the mechanical properties of graphene reflects the elasticity of graphene. This significant enhancement of UTS with the presence of graphene cannot be simply considered as a simple rule of mixture. The presence of graphene flakes in composites has a great impact on composite design criteria.

[0083] This strengthening is due to the transfer of load from the matrix material to the graphene particle reinforcement, which also plays a load-bearing role rather than just controlling dislocation motion. The strength decreases slightly due to agglomeration of higher concentrations of graphene (3%), while lower concentrations are insufficient to withstand the matrix load; the stress-strain curves produced during the experiment are shown below 9, and it can be assumed that the fine particles of graphene are similar to precipitation hardening systems in the matrix material, forming small clusters that may produce local strains that are effectively transferred to the reinforcement. The degree of strengthening depends on the distribution of the particles in the ductile matrix; in addition to the shape of the particles, the reinforcement can also be described by the average particle size, volume fraction and average particle spacing.

[0084] Graphene prevents the propagation of cracks, thereby strengthening the matrix by absorbing dislocations in the matrix material; this reinforcement slows down the motion of dislocations in two different ways: the reinforcement particles can be cut by the dislocations, or the graphene particles can resist the dislocations.

[0085] The planar 2D structure of graphene interlocks the magnesium matrix, creating a diffusion-free bond between the two, increasing dislocation density through thermal differences between the filler and the matrix; this 2D planar structure can take the form of wrinkles, and when the material is loaded, the load transfer either tries to unfold the graphene particles or expand them. Another predictable reason for the increase in strength is the grain fineness of the graphene particles due to heat absorption, which can be observed in the microstructure.

[0086] Hall-Petch grain refinement strengthening in composite materials can be described by formula (3)

[0087] σ_y∝√d(3)

[0088] Where d is the average diameter of the grain size.

[0089] Other strength mechanisms may be intrinsic properties of the alloys, attributed to stacking fault energy, coherence strain, lattice friction stress, modulus effects, ordered structure, and interfacial energy.

[0090] The strain field generated by the difference between the particle and the matrix given by Mott and Nabarro is the basis for strengthening. The increase in yield strength is determined by equation (4)

[0091] Δσ = 2 (G × ε × f) (4)

[0092] Where f is the volume fraction (of the dispersed phase) and ε is the measured value of the strain field.

[0093] The energy of a dislocation depends linearly on the local modulus, and particles with a modulus significantly different from that of the matrix material will increase or decrease in energy when passing through a dislocation. This strengthening effect is given by equation (5)

[0094]

[0095] where f is the volume fraction (dispersed phase) and r is the radius of the particle.

[0096] In most alloys, the modulus difference is not sufficient; however, the criterion for modulus difference is met by reinforcement, resulting in a possible strong reinforcement effect. The above equation given by Hirsch and Kelly was derived for the case of spherical reinforcements, but the maximum strength due to surface effects comes from thin plate-like (planar) reinforcements similar to the planar structure of graphene.

[0097] Significant improvement in ultimate tensile strength was achieved, resulting in longer nominal ductility. The strength enhancement of these composites has been mainly attributed to dislocation enhancement, optimal grain refinement, and various other models. Orowan strengthening mechanism may also contribute to the enhanced strength of the composites. Extrusion process also improves tensile strength; however, understanding the contribution of two or more mechanisms acting in combination remains challenging.

[0098] Tensile fracture morphology analysis

[0099] Fig.10 SEM images showing tensile fracture pitting fracture characterized by almost equiaxed cup-shaped depressions showing the behavior of ductile composites due to the agglomeration of microvoids in the molecular mixing level. Ductile fracture characteristics were observed for the 2wt% Gr grade. This can be attributed to the uniform distribution of graphene inside the grains, providing rigid interfacial regions; these interfacial regions act as both dislocation initiation sites and dislocation sinks, while pinning dislocation motion. In the 2wt% Gr composite, the uniform distribution prevents the accumulation of reinforcement at the grain boundaries, thereby demonstrating good strength through dislocation pinning without losing the ductility of the composite. Anything below 2wt% Gr shows dispersion, exposing more of the matrix material, illustrating more matrix properties. While greater than 2%, i.e. 3%, graphene reinforcements consist of pits and tear ridges, known as quasi-cleavage fractures, which are due to agglomeration in the grain boundaries resulting in weak tensile strength due to weaker interfacial bonding.

[0100] The distribution of graphene is clearly visible at all reinforcement percentages, forming the inherent characteristics of alloying elements in a multiphase structure, which also contributes to the strength of the composite. It reveals that the added graphene is randomly arranged in all directions. At 2%, fine dispersion reinforcement is achieved, with shallow pits, showing good ductility without losing strength. The pulling and tearing of graphene shows that the load is transferred from the matrix to the reinforcement, and partially pulled-out graphene is also observed, which further confirms the transfer of load from the matrix to the graphene.

[0101] Hardness evaluation and analysis of composite materials

[0102] Fig.11The comprehensive hardness of different grades of magnesium alloy composites reinforced with graphene is shown and it is clear from the data that the highest hardness values ​​are exhibited at 2wt% graphene and the lowest is at 1wt% graphene. There is also an overall increase in the hardness of graphene reinforced magnesium compared to the basic standard alloy hardness values. The increase in hardness can basically be related to the grain fineness of the composites observed in the microstructural analysis. Graphene acts as a grain refiner due to the difference in thermal interface properties and also acts as a void filler, which can further inhibit dislocation movement and improve the strength and durability of the material. The increase in hardness related to tensile strength is due to the strain hardening that the composites undergo during the extrusion process. The effect of strain hardening also improves the morphology of the reinforcement and matrix bonding.

[0103] The present invention has characterized the properties of magnesium-based graphene composites in detail, such as spectroscopy, XRD, EDS, EBSD, FE-SEM and HR-TEM analysis, determined the metallurgical properties, chemistry and formation of harmful phases, and studied mechanical properties such as tensile and hardness. The results of characterization and mechanical evaluation are compared with the requirements of future clinical intravascular stent materials.

[0104] Nanosheet analysis of graphene at higher magnifications shows that graphene is a two-dimensional sheet structure; graphene has a huge surface area and good wettability, and plays a key role in reinforcing materials as a matrix material. When considering use in the aerospace field, graphene can become a potential reinforcement material.

[0105] The present invention successfully prepared magnesium-based graphene composite materials. Through EBSD spectra and HR-TEM, it was found that the enhanced particles were evenly distributed, and the EBSD of 2wt% Gr showed more uniform particle dispersion; however, higher wt% Gr showed grain boundary agglomeration. Microwave processing and hot extrusion provide simplicity for composite material processing, making it more potential, and applications in fields such as aerospace can be considered in addition to the biomedical field.

[0106] Graphene remains as a heterogeneous particle by not reacting with the phases and alloying elements present in the microstructure, which can also be verified in FTIR spectroscopy and TEM. XRD, EDS and FTIR confirm the presence of graphene as a reinforcement material is intact and there is no formation of carbides. This non-reactivity of graphene is achieved by microwave treatment because the process is very fast and the heat is achieved from the core of the composite material.

[0107] The magnesium alloy reinforced by 2wt% graphene has a maximum yield strength. Due to its inherent alloy properties, its performance is superior to other alloys. The maximum tensile yield strength of 2% Gr is 321.17MPa. The hardness value with 2% graphene is the highest, and the hardness with 1% graphene is the lowest; the hardness of +2% Gr is the highest at 95HRB, and the hardness of +1wt% Gr is the lowest at 63HRB; the pulling and tearing of graphene indicates that the load has shifted from the matrix to the reinforcement, and partially pulled-out graphene is also observed, which further confirms the shift of load from the matrix to the graphene; the combined mechanism, microwave sintering process and hot extrusion process (compared with hot rolling process) are potential and perfect conditions for converting the prepared composite materials into important applications in fields other than medicine.

[0108] The preparation technology of the magnesium-based graphene composite material provided by the present invention can adjust the performance of the composite material by controlling the addition amount of graphene, the temperature and time of the heating reaction, the conditions of high-pressure deposition, etc. At the same time, the use of organic solvents and coupling agents can improve the dispersibility and compatibility of graphene with magnesium powder, zinc powder and calcium powder, and improve the performance of the composite material. The preparation technology has the advantages of simple process, low cost, high efficiency, etc. The prepared magnesium-based graphene composite material has excellent mechanical properties, thermal conductivity and electrical conductivity, and can be widely used in the fields of medicine, aerospace, automobiles, electronic products, etc.

[0109] The above technical solutions only reflect the preferred technical solutions of the technical solutions of the present invention. Some changes that may be made to certain parts thereof by technicians in this technical field all reflect the principles of the present invention and fall within the protection scope of the present invention.

Claims

1. A method for preparing a magnesium-based graphene absorbable stent composite material, characterized in that: The following steps are involved: Step 1: ultrasonic treatment of graphene; Step 2: Preparation of raw materials of magnesium-based materials; Step 3: ball milling; Step 4: vacuum drying; Step 5: Composite die pressing; Step 6: microwave sintering; Step 7: high pressure synthesis; Step 8: Solid temperature extrusion.

2. The method for preparing a magnesium-based graphene absorbable stent composite material according to claim 1, characterized in that: In the step 1, graphene includes graphene materials of different properties such as multilayer graphene oxide (MGO), multilayer graphene nanosheets (GNS), and carbon nanotubes (CNT), and fine-layer graphene is ultrasonically treated and extracted, and the graphene is dissolved in ethanol (100-200 mg / ml) and ultrasonically dispersed for 1 hour.

3. The method for preparing a magnesium-based graphene absorbable stent composite material according to claim 1, characterized in that: In the step 2, the magnesium-based material pure magnesium and magnesium alloys of various components, the ultrasonically treated graphene and a certain proportion of pure magnesium or magnesium alloy powder are mixed to obtain a magnesium-based graphene mixture, the graphene content is usually 0.1-3wt%, and appropriate amounts of water and ethanol are added as media (the ratio of ethanol to magnesium alloy is 1-2g / ml), and stirred for 60-120 minutes to obtain a uniform slurry.

4. The method for preparing a magnesium-based graphene absorbable stent composite material according to claim 1, characterized in that: In the step three, the magnesium-based graphene mixture is placed in a ball mill, and appropriate amounts of water and ethanol are added as media, the ball-to-material ratio is 10:1, the ball milling speed is 300 rpm, and the ball milling time is 1-3 hours; a 10 mm tungsten carbide ball is used.

5. The method for preparing a magnesium-based graphene absorbable stent composite material according to claim 1, characterized in that: In the step 4, vacuum drying is performed at 80° C. for 2 hours.

6. The method for preparing a magnesium-based graphene absorbable stent composite material according to claim 1, characterized in that: In the step 5, a homogeneous composite mixture with different graphene percentages (such as 1wt%, 2wt%, and 3wt%) is mixed with a zinc stearate binder and polyvinyl alcohol (PVA) as a functional agent, and compacted with a steel mold at a pressure of 500MPa for 3-5min to obtain a certain size such as of the green body.

7. The method for preparing a magnesium-based graphene absorbable stent composite material according to claim 1, characterized in that: In the step six, the green body is sintered in a microwave oven for 15-30 minutes in an environment where argon inert gas continuously exists.

8. The method for preparing a magnesium-based graphene absorbable stent composite material according to claim 1, characterized in that: In step seven, combined with high pressure synthesis technology, in a high pressure reactor, the temperature is 300-500° C., the pressure is 1000-5000 psi, and the synthesis time is 2-12 hours.

9. The method for preparing a magnesium-based graphene absorbable stent composite material according to claim 1, characterized in that: In the step eight, hot extrusion is performed at 300-400° C., an extrusion speed of 1-2 mm / Sec, and an extrusion ratio of 11:1 to eliminate porosity and increase the density of the composite material, and finally obtain the required wire.

10. The method for preparing a magnesium-based graphene absorbable stent composite material according to claim 1, characterized in that: The prepared magnesium-based graphene composite materials are used in related technical fields such as medical, aerospace, automobiles and electronic products.

Citation Information

Cited By

  • Design method for improving thermal performance of composite material by regulating and controlling cluster types and number

    CN120296994A